2020
DOI: 10.1080/24704067.2020.1751675
|View full text |Cite
|
Sign up to set email alerts
|

From Rags to Riches: Business Model Innovation Shifts in the Ecosystem of the Chinese Super League

Abstract: The Chinese Super League (CSL) has witnessed unprecedented growth in recent years via evolutions in Chinese football clubs' business models and the league environment.This paper analyses business model innovation (BMI) in the light of changing ecosystem factors via a case study of the Guangzhou Evergrande Taobao FC. It analyses the types of BMI and finds that BMI constancy and novelty are key to the club's success.The study identifies policy and investors as the two ecosystem factors with the most significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In Europe, it has been found that investors in football clubs neither expect nor demand a financial return (14). In the East, massive capital investments from Evergrande FC and other CSL clubs backed by real estate firms boosted the CSL's popularity (9,15). We argue that the case for a causal effect running from high club debt to strong CSL growth in the examined period is highly probable.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In Europe, it has been found that investors in football clubs neither expect nor demand a financial return (14). In the East, massive capital investments from Evergrande FC and other CSL clubs backed by real estate firms boosted the CSL's popularity (9,15). We argue that the case for a causal effect running from high club debt to strong CSL growth in the examined period is highly probable.…”
Section: Discussionmentioning
confidence: 78%
“…Since December 2018, shadow rates have tightened substantially from cycle lows, and real estate entrusts, which issued shadow banking instruments and garnered considerable funds for the real estate industry's operations, including football investment, have plummeted (35). Meanwhile, in 2019, the Chinese Football Association implemented a series of regulatory frameworks, including strict wage limits (15), club names that must be not commercial (36), and club equity restructuring (37). These restrictive regulatory policies further amplified the negative effect of tightening monetary policy, thus crowding real estate enterprises out of CSL.…”
Section: Discussionmentioning
confidence: 99%
“…Financial and geopolitical challenges cloud China's image as a reliable economic actor. This may impact on its cultural and diplomatic sway in tandem (Liu, Skinner & Grosman, 2020;Sullivan, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Financial and geopolitical challenges cloud China's image as a reliable economic actor. This may impact on its cultural and diplomatic sway in tandem (Liu, Skinner & Grosman, 2020;Sullivan, 2017).…”
Section: Discussionmentioning
confidence: 99%